MEIOTIC SYSTEM OF EMEX AUSTRALIS - A PROLIFIC WINTER ANNUAL WEED - RENU BALA; VEENU KAUL; AMJAD ALI (International Journal of Pharma and Bio Sciences, 2012)
Emex australis Steinh. is a prolific winter annual which has assumed the status of an obnoxious weed. It grows in wide range of climatic conditions and has a potential to spread to even more diverse habitats. The meiotic system of the plant is studied to ascertain the ability to spread. It was found that the vigor to adapt to different habitats is provided both by its breeding and meiotic systems, though the former contributes more to generation of variation. In meiotic system, moderate chromosome number provides for shuffling through independent assortment while small chromosome size and low recombination index have minor role to play.